2003
DOI: 10.1128/iai.71.1.260-266.2003
|View full text |Cite
|
Sign up to set email alerts
|

Entry of the Lymphogranuloma Venereum Strain ofChlamydia trachomatisinto Host Cells Involves Cholesterol-Rich Membrane Domains

Abstract: Chlamydiae are bacterial pathogens which develop strictly inside the epithelial cells of their hosts. The mechanism used by chlamydiae to enter cells is not well characterized; however, it is thought to consist of a receptor-mediated process. In addition, the formation of clathrin-coated pits appears to be dispensable for chlamydiae to be internalized by host cells. Clathrin-independent endocytosis has recently been shown to occur through cholesterol-rich lipid microdomains, which are characterized by detergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 49 publications
3
41
1
Order By: Relevance
“…To further investigate this hypothesis, we carefully tested whether C. trachomatis serovars L2, D, E, and K are associated with lipid rafts, caveolin, or GM1 during entry. In contrast to some published studies (18,25,36), we were unable to find evidence that C. trachomatis entry is associated with or requires lipid rafts.We first confirmed that acute depletion of plasma membrane cholesterol by the cholesterol-chelating agent M␤CD inhibits C. trachomatis entry. C. trachomatis was propagated as previously described (40).…”
contrasting
confidence: 55%
“…To further investigate this hypothesis, we carefully tested whether C. trachomatis serovars L2, D, E, and K are associated with lipid rafts, caveolin, or GM1 during entry. In contrast to some published studies (18,25,36), we were unable to find evidence that C. trachomatis entry is associated with or requires lipid rafts.We first confirmed that acute depletion of plasma membrane cholesterol by the cholesterol-chelating agent M␤CD inhibits C. trachomatis entry. C. trachomatis was propagated as previously described (40).…”
contrasting
confidence: 55%
“…This intriguing difference between strains may possibly be due to the recognition of and binding to different receptor molecules on host cell surfaces that, for serovar E, may be enriched or clustered in some regions or microdomains of polarized epithelial cell apical membranes, such as lipid rafts or caveolae, proposed to be involved in serovar E but not in serovar L2 entry [19,20]. Although their role in chlamydial entry is still controversial [21][22][23], it is an interesting possibility, as many pathogens are known to interact with these membrane microdomains and that receptor molecules, such as membrane-associated estrogen receptors that locate to caveolae, have been implicated in serovar E attachment/entry [11,24]. In contrast, initial interactions of serovar L2 EB with host cell surfaces may occur via recognition of a broader range of host molecules or molecules widely represented throughout cell surfaces, such as heparan sulfate proteoglycans [25], and/or via Tarp-mediated pedestallike formation [26,27], a phenomenon shown to be more prevalent for serovar L2 than with serovar D [26] or serovar E [28].…”
Section: Discussionmentioning
confidence: 99%
“…The actin rearrangements that occur during entry are transient and may be terminated by secreted chlamydial effectors such as CT166, which glucosylates Rac1 (Thalmann et al 2010), or CT694, which interacts and colocalizes with AHNAK, an actin-binding protein (Hower et al 2009). Additional host factors that contribute to uptake into nonphagocytic cells include clathrin (Boleti et al 1999;Hybiske and Stephens 2007a) and cholesterol-rich microdomains (Norkin et al 2001;Jutras et al 2003;Stuart et al 2003;Gabel et al 2004). …”
Section: Mechanisms Of Chlamydia Invasion Of Epithelial Cellsmentioning
confidence: 99%